Comparative genomic and evolutionary relationship analysis in identification of Actinomyces naeslundii Probiotic properties-related proteins - Noor Afifah Hanin Mohamad (Kulliyyah of Nursing,International Islamic University Malaysia, 2021)
The genus Actinomyces encompasses a diversity of species that inhabit in human oral. Accordingly, their roles has come to debate as some claimed to cause actinomycosis, while the others claimed to give benefits, by inhibit the growth of Streptococcus mutans, thus prevent the formation of oral caries. The Actinomyces genus that are claimed to be benefial in inhibiting the oral caries is Actinomyces naeslundii NCTC 10301. The objective of the study is to determine the probiotic-related proteins from Actinomyces naeslundii using bioinformatic tools. Here, genome comparison of A. naeslundii with the 26 known-probiotics was analyzed using the Mauve software. From the comparison, probiotic of Bifidobacterium sp. were found to have most similarity with A. naeslundii compared to the other probiotics. Thus, sequences of 16s rRNA afford a means to establish phylogenetic tree with the A. naeslundii, 26 known probiotics and 33 oral pathogens. This yield of tree, using the ClustalW and Mega-X software could provide view of species evolutionary relationship between A. naeslundii, probiotics and oral pathogens. The tree shows A. naeslundii was clustered together with its own genus as well as with Bifidobacterium sp. EMBOSS Needle was used to interpret the percent similarities between 16 potential proteins of A. naeslundii with probiotics proteins of probiotic porperties. InterPro and Biocyc.org software were used to interpret the details function of similar proteins found in the genome comparison between A. naeslundii and Bifidobacterium sp. From the analysis, 9 proteins were shown to have probiotics properties. From all the analysis, it shown that protein chaperonin GroEL in A. naeslundii to have the highest percent of similarities and predicted to function as the probiotic properties, in response to wide variety of stimuli including heat and stress. This finding conclude that the role of A. naeslundii was to give more benefits to human oral rather than harm.